2013
DOI: 10.3892/ijo.2013.2053
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of mesenchymal stem-like cells in meningioma specimens

Abstract: Cells resembling bone marrow mesenchymal stem cells (BM-MSCs) have been isolated from glioma specimens; however, little is known about the existence of mesenchymal stem-like cells (MSLCs) in meningioma. Here, we hypothesized that cells similar to BM-MSCs exist in meningioma specimens and sought to investigate whether these putative meningioma stroma MSLCs (MS-MSLCs) could be isolated. To this end, we cultured fresh meningioma specimens using the same protocols as used previously to isolate BM-MSC. Cultured cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
(99 reference statements)
0
15
0
Order By: Relevance
“…Therefore, the researches about treatment to glioblastoma are focus on GSCs. Till now, there is not an acknowledged identification criteria of GSCs; but a series of experimental standards including the existence of specific bio-markers for stem cell, the potentiality for multidirectional differentiation and self-renewal, are extensively accepted [11][12][13]. In this study, the neurospheres isolated from glioblastoma cell line revealed the forementioned characteristics of GSCs, for instance, the neurospheres could differentiate to astrocyte and neuron, and isolated single cell from neurospheres could form subspheres.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the researches about treatment to glioblastoma are focus on GSCs. Till now, there is not an acknowledged identification criteria of GSCs; but a series of experimental standards including the existence of specific bio-markers for stem cell, the potentiality for multidirectional differentiation and self-renewal, are extensively accepted [11][12][13]. In this study, the neurospheres isolated from glioblastoma cell line revealed the forementioned characteristics of GSCs, for instance, the neurospheres could differentiate to astrocyte and neuron, and isolated single cell from neurospheres could form subspheres.…”
Section: Discussionmentioning
confidence: 88%
“…Previous work has shown the presence of cancer stem cells in meningioma cell lines [2831], but did not associated novel markers with growth dynamic. In culture, both NG type and G type cell lines had cells co-positive for stem cell markers, however, NG cell lines showed increased number of CD133+ Sox2+ and AGR2+ BMI1+ co-positive cells.…”
Section: Discussionmentioning
confidence: 97%
“…Early passaged cell cultures represent the “Central dogma” of patients’ tumors more faithfully than long term commercial cultures, yet very few attempts have been made to use such cells for pharmacological testing in meningiomas [21]. Growth associated receptors and cancer stem cells (CSCs), cancer cells that express stem cell markers and are highly tolerant to adverse growth conditions, have been identified in stable meningioma cell lines [2231], even in cultures that have been sustained in a wide range of media conditions [27, 32, 33]. However, identified meningioma CSCs in primary cell lines are not commonly associated with drug resistance, possibly because such studies require abundant number of cells which is often restricted by the size of excised tissues [34].…”
Section: Introductionmentioning
confidence: 99%
“…These non-tumorigenic cells were named to be glioma associated stem cells (GASC) (Bourkoula et al 2013), tumor associated mesenchymal stromal cells (TAMSC) (Hossain et al 2011), brain tumor derived-mesenchymal stem cell (BTD-MSC) (Behnan et al 2014) and tumor mesenchymal stem like cells (tMSLCs) (Kim et al 2011Kwak et al 2013;Lim et al 2013). It is reported that GASC plays a role to predict the progression of the low grade glioma (Bourkoula et al 2013), BTD-MSC is relevant to tumor progression (Behnan et al 2014) and MSCL is associated with the increase in angiogenesis (Shin et al Fig.…”
Section: Non-tumorigenic Stromal Cells In Gbmmentioning
confidence: 99%